2014
DOI: 10.12944/cwe.9.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Nitrate and Nitrite Pollution in Ground Water of Rural Areas of Lucknow, U.P., India

Abstract: The present world is facing problems with a wide variety of pollutants. Water pollution is a major global problem. It has been suggested that it is the leading worldwide cause of deaths and diseases and that it accounts for the deaths of more than 14,000 people daily in Lucknow Capital of Uttar Pradesh in India.Nitrate and Nitrite pollution is one of groundwater's most commonly identified contaminants, an indicator of serious pollution as they are associated with septic waste and agricultural endeavours, leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The main forms of nitrogen in aquatic ecosystems are total nitrogen, ammonium nitrogen (NH 4 + –N), and nitrate nitrogen (NO 3 − –N and NO 2 − –N) [ 1 ]. In recent years, excess nitrogen in water bodies, especially NO 3 − –N, has led to major ecological problems [ 2 ]. In addition, NO 3 − –N in drinking water can be converted to NO 2 − –N by the commensal bacteria in the mouth and digestive tract, which is harmful to the health of adults and children.…”
Section: Introductionmentioning
confidence: 99%
“…The main forms of nitrogen in aquatic ecosystems are total nitrogen, ammonium nitrogen (NH 4 + –N), and nitrate nitrogen (NO 3 − –N and NO 2 − –N) [ 1 ]. In recent years, excess nitrogen in water bodies, especially NO 3 − –N, has led to major ecological problems [ 2 ]. In addition, NO 3 − –N in drinking water can be converted to NO 2 − –N by the commensal bacteria in the mouth and digestive tract, which is harmful to the health of adults and children.…”
Section: Introductionmentioning
confidence: 99%
“…P mining from P rocks and P fertilizer is a cause of water pollution. Too much N and phosphorous in water cause algae to grow and lead to the eutrophication phenomenon (Verma et al 2014). Va et al (2018) reported that domestic wastewater generated from various types of buildings had been recognized to be different to some extent.…”
Section: Introductionmentioning
confidence: 99%